Haematological values of Udah and Yankasa sheep in the northern Guinea savanna of Nigeria - Saror, D.I.; Schillhorn Veen, T.W. van (Springer, 1977)
Haematological values of healthy Yankasa and Udah sheep were determined to serve as baseline for clinical interpretation of haematological data from diseased local sheep. Values for Hb, PCV, RBC and WBC from the healthy flocks were similar, though lower than reported values for sheep in temperate zones except the WBC values which were higher. These parameters were lower in the infected flock and had a wider spread.